In-ovo imaging using ostrich eggs: biodistribution of F-18-FDG in ostrich embryos - Thomas Winkens; Thomas Winkens; Pauline Schweitzer; Olga Perkas; Christian Kühnel; Ferdinand Ndum; Marta Pomraenke; Marta Pomraenke; Julia Greiser; Julia Greiser; Martin Freesmeyer; Martin Freesmeyer (Experimental Biology and Medicine)
In-ovo imaging using ostrich eggs has been described as an alternative to animal testing using rodents. This approach is not considered an animal experiment and it does not require small-animal imaging devices as ostrich eggs provide good image quality on regular CT, MRI or PET used in humans. The aims of this study were 1) to describe methods of radiopharmaceutical injection, 2) to explore normal biodistribution of F-18-FDG during a 60-min list-mode-PET/CT examination and 3) to compare biodistribution in-ovo to existing literature considering chicken and rodents. Vessel access was successful in 54/78 ostrich eggs. Highest FDG-uptake was observed in epiphyseal plates (0.36 ± 0.06 IA%/g; range 0.29–0.48 IA%/g) and brain (0.25 ± 0.05 IA%/g; range 0.21–0.36 IA%/g). In-vivo activity distribution on PET and ex-vivo activity distribution (well counter) showed comparable results (Spearman’s Rho range 0.795–0.882). No significant differences were observed regarding previous isoflurane exposure. Normal biodistribution of F-18-FDG in ostrich embryos using a standard PET/CT system for humans was mainly found as expected with highest uptake in epiphyseal plates and brain which is comparable to results on rodents and chicken embryos. Isoflurane anesthesia did not reveal significant differences regarding organ uptake. The results of this normal distribution study allow for interpretation of future disease models (inflammation, tumor) in ostrich embryos using F-18-FDG as radiopharmaceutical.